-6=q-4/5(3-9)

Simple and best practice solution for -6=q-4/5(3-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=q-4/5(3-9) equation:


-6=q-4/5(3-9)

We simplify the equation to the form, which is simple to understand
-6=q-4/5(3-9)

Simplifying:
-6=q-0.8*(3-9)

Simplifying terms in parentheses
-6=q-0.8*(-6)

Reorder the terms in parentheses
-6=q+(+4.8)

Remove unnecessary parentheses
-6=+q+4.8

We move all terms containing q to the left and all other terms to the right.
-1q=+4.8+6

We simplify left and right side of the equation.
-1q=+10.8

We divide both sides of the equation by -01 to get q.
q=-10.8

See similar equations:

| 3m+4=18+m | | 6x+5=5x | | .20t-3=17 | | 3y+9x=3 | | 9(g+3)-2g+7= | | 9(-5-r)=10-2r | | 6.7x=52x+12.3 | | 7x+60=-23x | | x=20.5 | | -5(3t-4)=8(-2t+11) | | 3(v+1)+2=20 | | -5c+10=10c-120 | | 4=c | | 3x^3y-12xy=0 | | 5x+3(x-9)=-(5x+2)+1 | | x=17a+5 | | 2x(x+3)=2x+5 | | 5(2a-3)+2=4a+2(3a-6)-1 | | 2z^2-9z-200=0 | | 3(4x-1)=4(2x-3)+8 | | 9u-13u=-16 | | 4=-4.5+b | | 1-3x=2x+8v | | 4c-6+c=4-3c | | 11-3(r+1)=35 | | 2c^3+6c^2+56c= | | 4m+-2m=-12 | | 8y+2=5y-7 | | -5.6-4y-4.7-2y=-5y+4.6 | | 1.7(x+3)=2.1x+9.7 | | 8+7(b+2)=-3+6(b+5) | | C^2(2*c)=20 |

Equations solver categories